Highly Stable Nanocrystal Engineered Palladium Decorated Cuprous Oxide Photocathode for Hydrogen Generation. Issue 21 (8th September 2019) - Masudy‐Panah, Saeid; Khiavi, Negar Dasineh; Katal, Reza; Ten It, Wong; Saeedikhani, Mohsen; Rimaz, Sajjad; Ying, Wu; Xiao, Gong
Abstract: Photocorrosion stability and the discrepancy between optical absorption and carrier diffusion length of cuprous oxide (Cu2 O) thin films are the main limiting factors for hydrogen evolution and practical applications of Cu2 O photocathodes. In this paper, by nanocrystal engineering the Cu2 O optical absorbing thin film, the photocorrosion stability can be significantly improved. Furthermore, palladium (Pd) nanostructures are used to both act as a cocatalysis and address the discrepancy between optical absorption and carrier diffusion length of cuprous oxide and improve the photocatalytic activity of Cu2 O photocathodes. By tuning the crystal quality of thin Cu2 O film and Pd nanostructures through controlling the sputtering power of Cu2 O and in situ plasma of substrate, the impact of the degree of crystallinity of thin Cu2 O film and Pd nanostructures on photocorrosion stability and photocatalytic activity of prepared photocathodes are investigated in detail. Systematic characterization of prepared samples by using X‐ray diffraction, high‐resolution transmission electron microscopy, and scanning electron microscope analysis indicates that improving the crystallinity of deposited Cu2 O thin film and Pd nanostructures can significantly improve the photocorrosion stability and performance of Cu2 O based photocathodes. Abstract : The novelty of this work is nanocrystal engineering of Cu2 O thin film and Pd nanostructures for visible light driven electrochemical water splitting with high stability and enhanced performance of the photocathode. The nanocrystal engineering of Cu2 O and Pd nanostructures boost the overall performance of photoelectrocatalysis cell and enhance the stability of the photocathode.